Group Counseling’s Effectiveness Using Assertive Training to Reduce Bullying Victims' Anxiety in High School - Rahmat Dwi Putra Sadeli; Yeni Karneli (International Journal Labs, 2022)
The impact caused by bullying behavior is reducing student concentration, decreased learning achievement, difficulty socializing, children become timid, often anxious to mental disorders. One way that can be done to reduce bullying anxiety among students is to provide group counseling services using assertive training techniques. The purpose of this study was to reveal differences in bullying anxiety of experimental group students before and after participating in group counseling using assertive training techniques, bullying anxiety of control group students before and after participating in group counseling without special treatment, and to reveal differences in bullying anxiety of experimental group students who participated in group counseling using assertive training techniques with control groups without special treatment. This research is Quasi Experiment. The sample of this study was 12 students for the experimental group and 12 students for the control group. The sample technique used was purposive sampling. The statistical analysis of the data used in this study was nonparametric statistics. There was a significant difference in bullying anxiety in the experimental group before and after participating in group counseling services using assertive training techniques, there was a significant difference in bullying anxiety in the control group before and after being given group counseling services without special treatment, there were differences in bullying anxiety in the ex-group bullying anxiety. Group counseling services are provided using assertive training techniques with control groups provided group counseling services without special treatment. Thus, group counseling services using assertive training techniques are effective in reducing student bulllying anxiety.